Two-Element MIMO Crack Finger Microstrip Antenna for Hand-Held Devices - M. Elamin, Nassrin I.; A. Alabid, Loai A.; Gismalla, Mohammed; Al-Fadhali, Najib (Journal of Advanced Industrial Technology and Application, 2022)
in this paper, we studied the effect of mutual coupling between MIMO antennas and a method is proposed to reduce it between 2-element micro-strip MIMO antenna systems for handheld devices. To reduce mutual coupling between the MIMO antenna element a separate ground plane is designed and the two elements are positioned on the edges of the 2-element MIMO antenna system. A novel idea defined in order to reduce mutual coupling between the closely spaced micro-strip patch elements is adding finger shapes at the edge of each patch antenna to design a new crack finger micro-strip the fingers generate capacitance in between which improved the matching between the patch and the Micro-strip transmission line as well as the mutual coupling reduced from -25 dB to -40 dB. The simulation results showed that the 2-element MIMO system covered the frequency of 2.4 GHz, and the gain and directivity are 6.149 dB and 4.399All the simulations were carried out in CST Microwave Studio.